BRS 368RF: A glyphosate tolerant, midseason upland cotton cultivar for Northeast and North Brazilian cerrado - Barroso,Paulo Augusto Vianna (2017)
Abstract Cotton cultivar BRS 368RF was developed by EMBRAPA in a partnership with the Bahia Foundation, aiming to create high-yielding germplasm by adding transgenic traits addressed to Brazilian Savanna (cerrado) of the Northeast and North regions. BRS 368RF is a midseason cultivar and has yield stability and transgenic tolerance to glyphosate.